Effect of Preoperative Gabapentin With a Concomitant Adductor Canal Block on Pain and Opioid Usage After Anterior Cruciate Ligament Reconstruction. Issue 3 (1st March 2019) - Ahearn, Briggs; Kumar, Arun; Premkumar, Ajay; Samady, Heather; Gottschalk, Michael; Xerogeanes, John; Karas, Spero
Background: An adductor canal block (ACB) and preoperative oral gabapentin have each been shown to decrease postoperative pain scores and opioid usage in patients undergoing anterior cruciate ligament (ACL) reconstruction. Purpose/Hypothesis: This study evaluated the efficacy of preoperative gabapentin on postoperative analgesia in patients who received an ACB. We hypothesized that patients undergoing ACL reconstruction with an ACB who utilized a single dose of preoperative oral gabapentin would have decreased pain and opioid consumption in the 24 to 72 hours after surgery compared with patients who did not utilize gabapentin. Study Design: Cohort study; Level of evidence, 3. Methods: Between January and October 2016, patients at a single institution who underwent ACL reconstruction and received an ACB were identified. Patients who underwent surgery before May 2016 were placed in the control group, and patients seen after May 2016 received a preoperative dose of gabapentin and were placed in the gabapentin group. All patients completed a pain log via a smartphone application to record pain scores and opioid usage after surgery. Results: A total of 74 patients were identified: 41 in the gabapentin group and 33 in the control group. There were no significant differences between groups in demographics and operative characteristics. There were no differences in pain scores on postoperative day 1 (gabapentin vs control: 5.53 vs 5.56; P = .95), day 2 (4.58 vs 4.83; P = .59), or day 3 (4.15 vs 3.87; P = .59). The mean opioid consumption in oral morphine equivalents was not different on postoperative day 1 (gabapentin vs control: 47.2 vs 48.1; P = .90), day 2 (29.9 vs 33.5; P = .60), or day 3 (17.4 vs 18.7; P = .80). Conclusion: Preoperative gabapentin did not reduce pain scores or opioid usage in patients who received an ACB and underwent ACL reconstruction in this retrospective cohort study.